Use of GMDH for Investigation of Impact of Non-income Components on HDI - Savchenko, E.; Tutova, O. (Індуктивне моделювання складних систем, 2012)
Impact of macroeconomic indices on the development level of countries is analysed in the article. UN data about human development for 2011 are used. Countries are divided into groups according to UN methodology. The factors influencing on the development level for every group were chosen and analysed. Combinatorial GMDH algorithm was used to build models describing dependence of human development index on macroeconomic factors.